2014
DOI: 10.5455/ijmsph.2014.260620141
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in sexually transmitted infection (STI) clinic attendees - Current scenario

Abstract: Background: Currently, sexually transmitted infections (STIs) form a huge public health issue in the global scenario. STIs are commonly more active than other prevailing infections in the community amongst the sexually active population and the epidemiological profile is very distinct and more dynamic than other diseases. Aims & Objectives: To understand the changing scenario of STIs and also the non-STIs among patients attending the STI clinic at the tertiary care centre. Materials and Methods: This is a tert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 13 publications
4
18
0
Order By: Relevance
“…The Male-to-Female ratio of patients who presented to the clinic was 1:3.6, which is in broad concordance with the study done by Patel N et al 6 (1:2.4), but it is contrary to the study done by Nair TG et al 7 and Arakkal et al 8 where the male-tofemale ratio is 2:1. Such a high ratio in females is understandable from the fact that a major chunk of the patient fell under the category of vaginal candidiasis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The Male-to-Female ratio of patients who presented to the clinic was 1:3.6, which is in broad concordance with the study done by Patel N et al 6 (1:2.4), but it is contrary to the study done by Nair TG et al 7 and Arakkal et al 8 where the male-tofemale ratio is 2:1. Such a high ratio in females is understandable from the fact that a major chunk of the patient fell under the category of vaginal candidiasis.…”
Section: Discussionsupporting
confidence: 87%
“…8 A retrospective data analysis from 1994 to 1998 at Medical College, Trivandrum showed that the commonest STD was syphilis, both in men and women followed by genital herpes and condyloma acuminate. 8 In the present study an increase in the incidence of candidiasis and genital wart has been noted, while there is a decrease in the incidence of syphilis. Thus to conclude, sexually transmitted disease continues to be a major public health problem.…”
Section: Discussionmentioning
confidence: 99%
“…Similar higher incidence of candidal balanoposthitis had been reported by Sharma et al, [14] Arakkal et al, [15] Murugesh et al [16] and Siddappa et al [17] Its occurrence was found to be more common in the sexually active younger age group but a significant number of older patients above the age of 61 years were also affected as older age is one of the risk factor for it. [9] Diabetes mellitus was found to be the predisposing factor in 90.74% of our patients with candidal balanoposthitis.…”
Section: Discussionsupporting
confidence: 81%
“…Percentage of patients with herpes genitalis ranged from 2.3% to 32.8% in various studies across India. [ 1 2 3 5 6 7 8 9 ] Chancroid was the second most common ulcerative STI in our study in 79 (1.5%) patients. Although there was a rise in number of patients of chancroid and syphilis from 2008 to 2010, a declining trend was seen thereafter till 2015.…”
mentioning
confidence: 51%
“…Most common age group affected was between 25-44 years (55.13%) in both males and females which was similar to many other studies. [ 1 2 3 4 5 6 7 8 ] Twenty-one (0.4%) patients were homosexual, 40 (0.8%) were bisexual, and rest 5213 (98.8%) were heterosexual. These findings were similar to study conducted at Puducherry.…”
mentioning
confidence: 99%